Journal of burn care & research - Herndon, David N.; American Burn Association (Oxford : Oxford University Press, 2017)
Through original, peer-reviewed articles, 'Journal of Burn Care & Research' provides the latest information on advances in burn prevention, research, education, delivery of acute care, and research to all members of the burn care team.
Previously Journal of Burn Care and Rehabilitation from 1st Jan 1980 to 1st Jan 2005.
Description based on online resource; title from home page (viewed on April 20, 2018).
Keywords: Burns and scalds -- Research -- Periodicals